2020
DOI: 10.1055/s-0040-1712914
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adverse Events beyond Stroke and Bleeding with the ABC-Stroke and ABC-Bleeding Scores in Patients with Atrial Fibrillation: The Murcia AF Project

Abstract: Background The ABC (age, biomarkers, and clinical history)-stroke and ABC-bleeding are biomarker-based scores proposed to predict stroke and bleeding, but non-specificity of biomarkers is common, predicting different clinical events at the same time. We assessed the predictive performance of the ABC-stroke and ABC-bleeding scores, for outcomes beyond ischemic stroke and major bleeding, in a cohort of atrial fibrillation (AF) patients. Methods We included AF patients stable on vitamin K antagonists fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 51 publications
(50 reference statements)
0
30
1
Order By: Relevance
“…In addition, our ABC score is different from the previously published ABC-stroke and ABC-bleeding scores which were developed using age, biomarkers, and clinical history to predict outcomes in atrial fibrillation patients. 25 In Camelo-Castillo et al's study, both ABC-stroke and the ABCbleeding scores demonstrated a poor to moderate ability in predicting ischemic events (C-indexes: 0.54-0.64), but a good ability in predicting ACM (C-indexes > 0.70). Our ABC score only including three variables has strong ability to Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, our ABC score is different from the previously published ABC-stroke and ABC-bleeding scores which were developed using age, biomarkers, and clinical history to predict outcomes in atrial fibrillation patients. 25 In Camelo-Castillo et al's study, both ABC-stroke and the ABCbleeding scores demonstrated a poor to moderate ability in predicting ischemic events (C-indexes: 0.54-0.64), but a good ability in predicting ACM (C-indexes > 0.70). Our ABC score only including three variables has strong ability to Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, the clinical usefulness of biomarkers when they are evaluated alone may be only limited. In fact, a common criticism of biomarkers is their high variability and lack of specificity in different clinical settings [38][39][40]. However, an advantage of miRNAs compared to other biomarkers is their plasma stability, which makes them less likely to be altered due to acute conditions [9,41], even though results from miRNAs levels should be interpreted with caution and contextualized according to clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several papers focused on the use of biomarkers for risk stratification in AF, and their nonspecific nature, being reflective of a sick patient or a sick heart. 28,29 The updated systematic review on the association of antiphosphatidylserine/prothrombin antibodies with the autoimmune disorder antiphospholipid syndrome, may help identifying antiphospholipid syndrome patients otherwise negative for current tests. 30 The relevance of clinical conclusions also relies on the strength of the technique used.…”
Section: Refining Anticoagulation Treatment Choices Identifying and Tmentioning
confidence: 99%